(Liability of Liquidator in Liquidating a Shareholding Company (A Comparative Study - Bafageeh, Afnan; Alshreef, Naief (Journal of Economic, Administrative and Legal Sciences, 2019)
If the company reaches the expiration period for any reason of the expiration, it must first work on procedures which aim at ending the company’s process, pay the debts, collect the receivables, and transfer assets and real estate to cash to be distributed to partners. This is what is called liquidation. However, there must be a person who supervises the liquidation process and is responsible for it when facing partners, shareholders and others; and this is the liquidator. Accordingly, a liquidator is a person or a group of persons- natural or legal- who manages the company from the time that the company expires to the date of distribution of net liquidation to the partners or shareholders. However, the Egyptian Companies Law and the Saudi Companies Law did not specify the legal status of the liquidator with clear rules, such as the lack of clarity of the relationship between the liquidator of the company and the specification of certain conditions for the liquidator such as nationality, academic qualification and experience. In addition, the mechanism of isolating the liquidator was not specified in the Saudi system. Jurists differed about the powers of the liquidator. In fact, the powers of the liquidator have their own nature because they are determined in view of their purpose, not in view of the nature of the acts, so that the liquidator has the right to conclude all the acts necessary to complete the liquidation procedures. If the liquidator has powers and capacities, this means that the liquidator has duties that the legislator has approved, for example: repayment of the company’s debts, announcing the liquidation decision, and keeping books to record the liquidation. However, the Egyptian and Saudi Companies Law did not address the issue of the failure of some of the company’s creditors to apply for the satisfaction of their rights despite the call of the liquidator.